Carbon-based nanomaterials for the removal of emerging water pollutants - Danial, Wan Hazman; Hamzah, Nurasyikin; Ismail, Mohamad Wafiuddin; Aminudin, Nurul Iman; Shafiee, Saiful 'Arifin; Iqbal, Anwar (Royal Society of Chemistry, 2024)
The presence of emerging pollutants in water, including pesticides, cosmetics, pharmaceuticals, and unregulated compounds, has raised serious concerns due to their potential harm to human health and the environment, even at low concentrations. Traditional wastewater treatment methods struggle to completely eliminate these pollutants, necessitating innovative solutions. This chapter investigates the critical role of carbon-based nanomaterials, such as activated carbon nanoparticles, nanodiamonds, fullerenes, graphene and its oxides, carbon and graphene quantum dots, carbon nanotubes and nanofibers, and carbon aerogel, in addressing the challenge of emerging pollutant removal. Carbon nanomaterials are highlighted for their exceptional surface properties, adaptability, large surface area, adjustable structural modifications, and high chemical stability, making them ideal candidates for the removal of emerging pollutants. This chapter is expected to pave the way towards offering novel prospects for increasing the utilization of carbon-based nanomaterials and it may serve as a comprehensive resource for researchers, and policymakers, seeking to address the pressing issue of emerging water pollutants and enhance the protection of our vital water resources and public well-being.